Roadmap to Dystocia Management—Guiding Obstetric Interventions in Cattle - Nasreddine Larbi Smail; Mounir Adnane; Karen Wagener; Marc Drillich; Aspinas Chapwanya (Life)
Dystocia, or difficult labor, is a common complication during parturition in cattle that poses substantial risks to both dam and fetus. When the incidence is high on a farm level, it is a significant economic burden for dairy and beef enterprises. This review paper presents a comprehensive roadmap strategy to enhance decision-making in the management of dystocia in cows. The strategy encompasses early recognition and assessment, utilization of advanced diagnostic tools, and a range of medical and surgical interventions tailored to specific maternal and fetal causes of dystocia. The roadmap also integrates preventive measures to reduce the incidence of dystocia through genetic selection and optimized nutrition. By addressing the key challenges in dystocia management, such as resource constraints, timely intervention, and the need for continuous education, this strategy aims to improve health outcomes for cows and calves and reduce economic losses. Implementing this structured approach can facilitate better preparedness, efficient resource utilization, and improved overall livestock management, thereby promoting the sustainability and productivity of the cattle industry and addressing animal welfare aspects.